CHEMICAL RESEARCH AND BIOLOGICAL ACTIVITY OF PLANTS OF THE GENUS ATRAPHAXIS (A. SPINOSA) - Ikhsanov Y.S.,; Umbetova A.K.,; Burasheva G.Sh.,; Abidkulova K.T.,; Beyatli A.,; Sagatova S.N.,; Askanova D.K., (Academic Scientific Journal of Chemistry, 2020)
In this article identifies new sources of obtaining biological substances from plants of the genus Atraphaxis (A. spinosa) prepared in the Almaty region. According to well - known methods, the analysis of indicators and standards of raw material quality-humidity, total ash, sulphate ash, insoluble ash in 10% hydrochloric acid-was developed and carried out. Micro- and macroelements determined by atomic absorption spectroscopy. Analysis of the elemental composition shows that iron predominates from microelements, and sodium, potassium and calcium from macronutrients. Conditions for obtaining a biologically active complex from the aboveground part of Atraphaxis spinosa developed for the first time. The optimal conditions for obtaining the complex are extractant – 50% ethanol, the ratio of extractant and raw materials – 1:8, double extraction time – 48 hours, temperature – 22 - 26 °C. The lipophilic composition identified by chromatography-mass spectroscopy. Since lipophilic fractions of plant samples include such classes of compounds as fatty acids; mono-; di-; triglycerides, phospholipids, sterols, Sterol esters, glycolipids, fat-soluble vitamins, they can considered not only as nutritional products, but also as possible pharmacological agents. The content of lipophilic components – 26 organic compounds-was determined. It found that A. spinosa contains a large amount of di - (2-ethylhexyl) phthalate (54.66%) and β-sitosterol (13.11%). A complex study of plant resources as medicinal raw materials provides for the chemical study of biologically active substances and biological screening of extracts and individual compounds obtained from plants. In most cases, the extract showed a wide range of antibacterial activity against the used strains of microorganisms.